Calibration of a 3-Component External Balance for MAVs Wind Tunnel Research - Rafael Bardera; Ángel Antonio Rodriguez-Sevillano; Estela Barroso Barderas; Suthyvann Sor; Juan Carlos Matías García (Applied Sciences)
This paper presents a 3-component external balance, specifically designed, built, and calibrated at the National Institute for Aerospace Technology (INTA) for measuring aerodynamic forces on Micro Aerial Vehicles in the wind tunnel. The balance employs high-precision strain gauge cells as its load-sensing elements, strategically positioned in a metallic structure to measure lift force, aerodynamic drag force, and pitching moment. The entire calibration process of the balance, including the mathematical formulation to derive the calibration matrix and the calibration bench designed and manufactured for this purpose, is detailed in this paper. Moreover, the complete analysis of component interferences of the aerodynamic components and an assessment of the uncertainties inherent in the system are presented.